A Solution‐Processed High‐Performance Phototransistor based on a Perovskite Composite with Chemically Modified Graphenes. Issue 22 (4th April 2017) - Qian, Liu; Sun, Yilin; Wu, Mingmao; Xie, Dan; Ding, Liming; Shi, Gaoquan
Abstract : Phototransistors with a structure of a nitrogen‐doped graphene quantum dots (NGQDs)–perovskite composite layer and a mildly reduced graphene oxide (mrGO) layer are fabricated through a solution‐processing method. This hybrid phototransistor exhibits broad detection range (from 365 to 940 nm), high photoresponsivity (1.92 × 10 4 A W −1 ), and rapid response to light on–off (≈10 ms). NGQDs offer an effective and fast path for electron transfer from the perovskite to the mrGO, resulting in the improvement of photocurrent and photoswitching characteristics. The high photoresponsivity can also be ascribed to a photogating effect in the device. In addition, the phototransistor shows good stability with poly(methyl methacrylate) encapsulation, and can maintain 85% of its initial performance for 20 d in ambient air. Abstract : A solution‐processed phototransistor based on the composite of a perovskite modified by nitrogen‐doped graphene quantum dots (NGQDs) and mildly reduced graphene oxide shows a high photoresponsivity of up to 1.92 × 10 4 A W −1, a broad photodetection range of UV–vis–NIR, and good stability in air.